2017
DOI: 10.1002/ejlt.201600406
|View full text |Cite
|
Sign up to set email alerts
|

Avocado oil characteristics of Mexican creole genotypes

Abstract: Mexico is a major avocado producer and exporter, mainly the Hass variety, while the Mexican creole genotypes remain unexplored. We investigated the physicochemical characteristics, phenolics, and bioactivity of oils from six different Mexican avocado genotypes to increase their consumption and utilization. Oil content varied significantly among Mexican genotypes and increased linearly with dry matter content. Oils from Mexican creole genotypes varied significantly in UV absorbance and generally exhibited low s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 46 publications
2
17
1
Order By: Relevance
“…The PV and AV of CHOAO 1:2, CHOAO 1:3 and AO during storage at different temperatures (6, 25 and 45 °C) are shown in Table 2 and Totox kinetics are presented in Figure 2. In avocado oil, the results of PV and AV were lower than those previously reported in avocado oils from different varieties (Prescha et al, 2014;Espinosa-Alonso et al, 2017). No references about lipid oxidation in high concentrated Capsicum oleoresins were found.…”
Section: Lipid Oxidation During Storagecontrasting
confidence: 72%
“…The PV and AV of CHOAO 1:2, CHOAO 1:3 and AO during storage at different temperatures (6, 25 and 45 °C) are shown in Table 2 and Totox kinetics are presented in Figure 2. In avocado oil, the results of PV and AV were lower than those previously reported in avocado oils from different varieties (Prescha et al, 2014;Espinosa-Alonso et al, 2017). No references about lipid oxidation in high concentrated Capsicum oleoresins were found.…”
Section: Lipid Oxidation During Storagecontrasting
confidence: 72%
“…It was observed that the Mexican creole genotypes had a greater thermal stability, properties resistant to oxidation, and a greater phenolic content, in comparison with the commercial oil from the Hass variety. In addition, these varieties showed intense fluorescent peaks at 675 and 720 nm, as well as broad absorption bands centered at 465 and 510 nm, which can be used as an identification parameter for these oils [48].…”
Section: Composition Of Avocado Oilmentioning
confidence: 99%
“…The incorporation of avocado oil for a period of six days reflected an improvement in the postprandial profile of insulin, glycemia, total cholesterol, low-density lipoproteins, triglycerides, and inflammatory parameters, such as C-reactive protein (CRP) and interleukin-6 [63]. Avocado pulp oil (Mexican creole genotypes) has shown anti-inflammatory activity by inhibiting the enzymes COX 1 and COX 2 in a similar way to the drug, ibuprofen, and extra virgin olive oil [48]. Additionally, when avocado oil was added to vitamin B12 skin cream preparation, it was well tolerated and had the potential for long-term topical therapy of psoriasis [64].…”
Section: Biological Effectsmentioning
confidence: 99%
“…Extractions of avocado oil using organic solvents, centrifugation force, supercritical fluid, and cold‐pressing have been studied extensively in the past. However, chemical properties of the oil obtained following different extraction methods, particularly the qualities, bioactive phytochemicals, volatile components, and antioxidant capacities, have not been investigated.…”
Section: Introductionmentioning
confidence: 99%